2016
DOI: 10.1155/2016/6530410
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor-Derived CXCL1 Promotes Lung Cancer Growth via Recruitment of Tumor-Associated Neutrophils

Abstract: Neutrophils have a traditional role in inflammatory process and act as the first line of defense against infections. Although their contribution to tumorigenesis and progression is still controversial, accumulating evidence recently has demonstrated that tumor-associated neutrophils (TANs) play a key role in multiple aspects of cancer biology. Here, we detected that chemokine CXCL1 was dramatically elevated in serum from 3LL tumor-bearing mice. In vitro, 3LL cells constitutively expressed and secreted higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 49 publications
(49 reference statements)
6
68
0
Order By: Relevance
“…Recent evidence demonstrated that CXCL1 enhanced tumor growth via recruitment of neutrophils into the tumor microenvironment. For example, tumor cell-secreted CXCL1 promoted lung cancer growth via recruitment of neutrophils into tumor tissue in vivo (35). TNFα stimulates mesenchymal stromal cells to produce CXCR2 ligands that recruit CXCR2 + neutrophils into primary tumors in a mouse model of breast cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrated that CXCL1 enhanced tumor growth via recruitment of neutrophils into the tumor microenvironment. For example, tumor cell-secreted CXCL1 promoted lung cancer growth via recruitment of neutrophils into tumor tissue in vivo (35). TNFα stimulates mesenchymal stromal cells to produce CXCR2 ligands that recruit CXCR2 + neutrophils into primary tumors in a mouse model of breast cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…TNFα directly endorses tumor progression and metastasis . Furthermore, CXCL1 has been reported to facilitate lung cancer cell growth due to the recruitment of MDSCs and tumor associated neutrophils . Importantly, all of these factors were also found to be upregulated in K‐ras G12D ‐mutated lung alveolar type II (K) cells compared to WT cells or in tumor harboring lungs from KP mice compared to non‐tumorous lungs from KP mice.…”
Section: Discussionmentioning
confidence: 99%
“…48 Furthermore, CXCL1 has been reported to facilitate lung cancer cell growth due to the recruitment of MDSCs and tumor associated neutrophils. 13,49 Importantly, all of these factors were also found to be upregulated in K-ras G12D -mutated lung alveolar type II (K) cells compared to WT cells or in tumor harboring lungs from KP mice compared to non-tumorous lungs from KP mice. In agreement with this data, low mRNA expression levels of lL6, Tnfα and IL8 (the human orthologue to murine Cxcl1) were also associated with a better prognosis in lung AC patients harboring K-RAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of CXCL1 are elevated in CRC and increased levels are associated with tumor size, advancing stage and patient survival 37,38 . It was reported that CXCL1 could promote tumor growth by inducing angiogenesis and recruiting neutrophils into the tumor associated microenvironment 39,40 . CXCL1, most abundant secreted chemokine by tumor-associated macrophages (TAMs) have been implicated in the promotion of breast cancer growth and metastasis via activating NF-κB/SOX4 signaling 41 .…”
Section: Discussionmentioning
confidence: 99%